Can Total Wrist Arthroplasty Be an Option for Treatment of Highly Comminuted Distal Radius Fracture in Selected Patients? Preliminary Experience with Two Cases - Ingo Schmidt (Case Reports in Orthopedics)
We present two case reports of successful primary shortening of the forearm and total wrist arthroplasty (TWA) using the new angle-stable Maestro Wrist Reconstructive System (WRS) for treatment of highly comminuted distal radius fracture in selected autonomous patients. In a 56-year-old male patient with adequate bone stock, insertion of the noncemented Maestro WRS was combined with ulnar shortening osteotomy. In an 84-year-old female patient with poor osteoporotic bone stock, insertion of the radial cemented Maestro WRS was combined with ulnar head resection. Both patients could resume their work without additional surgery after TWA. At the 1-year follow-up, there were no changes in position of either implant without signs of loosening, no impingement, and no instability of the distal radioulnar joint or the distal ulna stump. All clinical parameters (DASH score, pain through VAS, and grip strength) were satisfactory. Both patients reported that they would have the same procedure again. Further experience is needed to validate this concept.